Posttransplant Lymphoproliferative Disorders in Neuronal Xenotransplanted Macaques. (March 2017) - Cavicchioli, L.; Ferraresso, S.; Westmoreland, S.; Kaliyaperumal, S.; Knight, H.; Crossan, C.; Scobie, L.; Danesi, A.; Vadori, M.; Trez, D.; Badin, R. Aron; Hantraye, P.; et al.
Posttransplant lymphoproliferative disorders (PTLDs) are a heterogeneous group of lymphoid proliferations that occur in the setting of depressed T-cell function due to immunosuppressive therapy used following solid organ transplantation, hematopoietic stem cell transplantation, and also xenotransplantation. In the present study, 28 immunosuppressed parkinsonian Macaca fascicularis were intracerebrally injected with wild-type or CTLA4-Ig transgenic porcine xenografts to identify a suitable strategy to enable long-term cell survival, maturation, and differentiation. Nine of 28 (32%) immunosuppressed primates developed masses compatible with PTLD, located mainly in the gastrointestinal tract and/or nasal cavity. The masses were classified as monomorphic PTLD according to the World Health Organization classification. Immunohistochemistry and polymerase chain reaction (PCR) analyses revealed that the PTLDs were associated with macaca lymphocryptovirus as confirmed by double-labeling immunohistochemistry for CD20 and Epstein-Barr nuclear antigen 2 (EBNA-2), where the viral protein was located within the CD20+ neoplastic B cells. In sera from 3 distinct phases of the experimental life of the primates, testing by quantitative PCR revealed a progression of the viral load that paralleled the PTLD progression and no evidence of zoonotic transmission of porcine lymphotropic herpesvirus through xenoneuronal grafts. These data suggest that monitoring the variation of macaca lymphocryptovirus DNA in primates could be used as a possible early diagnostic tool for PTLD progression, allowing preemptive treatment such as immunosuppression therapy reduction.